1989
DOI: 10.1111/j.1471-4159.1989.tb10906.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Size of the γ‐Aminobutyric AcidA Receptor Purified from Mammalian Cerebral Cortex

Abstract: The hydrodynamic behaviour of both the soluble and purified gamma-aminobutyric acidA (GABAA) receptor of bovine or rat cerebral cortex has been investigated in solution in Triton X-100 or in 3-[(3-cholamidopropyl)-dimethylammonio]-1-propanesulphonate (CHAPS). In all the hydrodynamic separations made, it was found that the binding activities for GABA, benzodiazepine, and (where detectable) t-butylbicyclophosphorothionate comigrated. Conditions were established for gel exclusion chromatography and for sucrose de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 37 publications
5
23
0
1
Order By: Relevance
“…Together, these results demonstrate that Q67 and S68 within the ␣1 subunit are critical in mediating assembly with ␤3 to form 9S complexes, representing functional cell surface receptors (Mamalaki et al, 1987(Mamalaki et al, , 1989Hadingham et al, 1992;Gorrie et al, 1997;Tretter et al, 1997). (9E10) ␣1 (HY) subunits appear to oligomerize less efficiently with (FL AG) ␤3 compared to (9E10) ␣1 and are rapidly degraded as previously described for unassembled wild-type ␣1 subunits (Gorrie et al, 1997).…”
Section: Reduced Oligomerization Of (9e10) ␣1 (Hy) With the ␤3 Subunitmentioning
confidence: 64%
See 1 more Smart Citation
“…Together, these results demonstrate that Q67 and S68 within the ␣1 subunit are critical in mediating assembly with ␤3 to form 9S complexes, representing functional cell surface receptors (Mamalaki et al, 1987(Mamalaki et al, , 1989Hadingham et al, 1992;Gorrie et al, 1997;Tretter et al, 1997). (9E10) ␣1 (HY) subunits appear to oligomerize less efficiently with (FL AG) ␤3 compared to (9E10) ␣1 and are rapidly degraded as previously described for unassembled wild-type ␣1 subunits (Gorrie et al, 1997).…”
Section: Reduced Oligomerization Of (9e10) ␣1 (Hy) With the ␤3 Subunitmentioning
confidence: 64%
“…Quantitation of the gradients revealed that both proteins exhibited 9 S sedimentation coefficients, as previously described for functional GABA A receptors composed of ␣␤ or ␣␤␥ subunits (Fig. 6 A,B; Mamalaki et al, 1987Mamalaki et al, , 1989Hadingham et al, 1992;Gorrie et al, 1997;Tretter et al, 1997). In contrast, unassembled ␣ or ␤ subunits have 5 S sedimentation coefficients (Gorrie et al, 1997;Tretter et al, 1997).…”
Section: Reduced Oligomerization Of (9e10) ␣1 (Hy) With the ␤3 Subunitmentioning
confidence: 76%
“…Thus the difference observed in the size of the photoaffinity-labelled sulfonylurea receptor determined by gel filtration chromatography and SDS-PAGE (166 kDa vs. 141 kDa) may be accounted for by the shape of the receptor being dissimilar from that of the proteins employed to calibrate the gel filtration matrix. In addition, the detergent micelle associated with the receptor may also contribute to the higher molecular weight observed with this method (for example see [19]). We therefore conclude that the unlabelled and photoaffinity-labelled receptors have similar molecular weights and thus that photoaffinity labelling does not lead to cross-linking of receptor subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor is a complex multi-subunit protein which possesses aUosteric binding sites for the anxiolytic benzodiazepines, the barbiturate drugs and a group of compounds called collectively the chloride channel ligands which include the convulsant compounds tbutylbicyclophosphorothionate (TBPS) and picrotoxin [1]. The GABAA receptor has been purified to apparent homogeneity from several vertebrate species and it has been shown to consist of two polypeptide chains, the cr subunit of 53 kDa and [7]. The ce subunit of the purified receptor is specifically photoaffinitylabelled by the benzodiazepine, [3H]flunitrazepam [2,4,8], whereas it is predominantly the/3 subunit which is specifically photoaffinity-labelled by the GABA agonist, muscimol [9,10].…”
Section: Introductionmentioning
confidence: 99%